2015
DOI: 10.1177/0954405415604314
|View full text |Cite
|
Sign up to set email alerts
|

Integrated dynamic cell formation with operator assignment and inter-cell layout problems: A mathematical model

Abstract: Designing a cellular manufacturing system involves four major decisions: cell formation, cellular layout, operator assignment and cellular scheduling which should be considered, simultaneously. This article presents a new mathematical model to solve the cell formation, operator assignment and inter-cell layout problems, concurrently. The objectives of proposed model are minimization of inter–intra cell part movements, machine relocation cost and operator-related issues including hiring, firing, training and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…To solve the problem, a hybrid genetic algorithm augmented ε -constraint method was proposed. Learning effect and flexibility of workers were discussed by Sadeghi et al 34 where a nonlinear mathematical model was proposed to solve the dynamic CF problem. Inter-/intracellular movements, machine relocation cost and worker-related costs such as hiring/firing/training were considered in the model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the problem, a hybrid genetic algorithm augmented ε -constraint method was proposed. Learning effect and flexibility of workers were discussed by Sadeghi et al 34 where a nonlinear mathematical model was proposed to solve the dynamic CF problem. Inter-/intracellular movements, machine relocation cost and worker-related costs such as hiring/firing/training were considered in the model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another symmetric solution may occur when the number of parts assigned to the cells is equal as in example 2 in Table 1. In this case, constraint (34) does not help to prevent the symmetry since the part numbers are already equal. For a situation like this, constraint (35) ranks the number of machine assignments to the cells in the descending order to prevent the formation of identical solutions such as in example 2.…”
Section: Symmetry Breaking Constraintsmentioning
confidence: 99%
“…The design of a CM usually starts with the CF and then follows by the Facility Layout (FL) and scheduling. 8 The majority of the studies conducted on the CM design have only focused on one of these decisions; examples of studies in this relation can be found. 917 However, it should be noted that these decisions are highly inter-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The robustness and performance of the mathematical model are explained in terms of an industrial case from a typical equipment manufacturer. Sadeghi et al 56 minimized machine relocation cost, inter-intra cell part movements as well as firing, hiring, training and salary costs using a proposed mathematical model. Their model considered operator assignment, cell formation and inter-cell layout problems, simultaneously.…”
Section: Introductionmentioning
confidence: 99%